Solid pseudopapillary tumor of pancreas: A case report and review of literature - Gursev Sandlas; Charu Tiwari (Indian Journal of Medical and Paediatric Oncology)
Solid pseudopapillary neoplasm of the pancreas is one of the rarest forms of pancreatic neoplasm. It was also known as Franz's tumor or Hamoudi tumor until WHO labeled it as solid pseudopapillary tumor (SPT) in 1996. It typically affects young non-Caucasian females in their second or third decade of life. Treatment involves complete excision of the tumor which results in complete cure in majority of the cases. We present here a report of 11-year-old girl with SPT and also do a review of literature for this rare tumor.